2023
DOI: 10.3390/nu15040958
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake and Arterial Hypertension: Retelling of a Multifaceted Story

Abstract: Alcoholic beverages are common components of diets worldwide and understanding their effects on humans’ health is crucial. Because hypertension is the leading risk factor for cardiovascular diseases and all-cause mortality, the relationship of alcohol consumption with blood pressure (BP) has been the subject of extensive investigation. For the purpose of this review, we searched the terms “alcohol”, “ethanol”, and “arterial hypertension” on Pubmed MeSH and selected the most relevant studies. Short-term studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 106 publications
1
5
0
1
Order By: Relevance
“…The same conclusion has been drawn by other studies, which have shown that despite some variability between genders and among different ethnic groups, sustained alcohol intake above 30 g per day significantly, and dose-dependently, increases the risk of hypertension [48].…”
Section: Micronutrientssupporting
confidence: 86%
“…The same conclusion has been drawn by other studies, which have shown that despite some variability between genders and among different ethnic groups, sustained alcohol intake above 30 g per day significantly, and dose-dependently, increases the risk of hypertension [48].…”
Section: Micronutrientssupporting
confidence: 86%
“…In addition, these study outcomes could be an essential tool to highlight the correlation between alcohol and arrhythmias, which can be fatal. Further prospective studies are necessary to improve knowledge of risk factors for the development of structural and molecular modifications of vascular endothelium and cardiac structure [ 100 , 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms such as shared risk factors, systemic inflammation, oxidative stress, and endothelial dysfunction may influence this bidirectional relationship ( Ganz et al ., 2011 ; Wang et al ., 2021 ). The regional heterogeneity in hypertension prevalence may be attributed to differences in the level of risk factors such as physical inactivity, alcohol consumption, high sodium intake, and low potassium intake ( Mills, Stefanescu and He, 2020 ; Zhou et al ., 2021 ; Vacca et al ., 2023 ). Despite the rising prevalence of hypertension, particularly in SSA countries, there are few comprehensive assessments for hypertension early detection and treatment ( Okello et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%